2014
DOI: 10.1007/s10571-014-0093-2
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin Protects Hippocampal Neurons Against Cell Death in Pilocarpine-Induced Seizures Through Antioxidant and Anti-Apoptotic Mechanisms

Abstract: Puerarin extracted from Radix puerariae has been shown to exert neuroprotective effects. However, it is still not known whether puerarin protects hippocampal neurons against cell death in pilocarpine-induced seizures. In this study, we found that pretreatment with puerarin significantly attenuated the neuronal death in the hippocampus of rats with pilocarpine-induced epilepsy. In addition, puerarin decreased the level of seizure-induced reactive oxygen species in mitochondria isolated from the rat hippocampi. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In addition, puerarin significantly prevented 1-methyl-4-phenylpyridinium (MPP + )-induced neurotoxicity in PC12 cells through inhibition of the c-Jun N-terminal kinase (JNK) signaling pathway (18). Furthermore, puerarin exerted a protective effect against epilepsy-induced brain injury through antioxidant and anti-apoptotic mechanisms (19). In line with these findings, puerarin also prevented amyloid β-induced neurotoxicity in PC12 cells.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition, puerarin significantly prevented 1-methyl-4-phenylpyridinium (MPP + )-induced neurotoxicity in PC12 cells through inhibition of the c-Jun N-terminal kinase (JNK) signaling pathway (18). Furthermore, puerarin exerted a protective effect against epilepsy-induced brain injury through antioxidant and anti-apoptotic mechanisms (19). In line with these findings, puerarin also prevented amyloid β-induced neurotoxicity in PC12 cells.…”
Section: Discussionmentioning
confidence: 64%
“…Puerarin, known as Ge-gen in Chinese, is isolated from Radix puerariae and has protective effects on the nervous and cardiovascular system to prevent osteoporosis, liver injury and inflammation (7). An increasing body of evidence has indicated that puerarin has anti-apoptotic effects and mitigated apoptosis in multiple cell types, including neurons, microglia, osteoblasts and cardiomyocytes (8)(9)(10)(11). A previous study reported that puerarin protected PC12 cells against β-amyloid-induced cell injury, which was associated with its antioxidant effects (12).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with E 2 , PME, or PU decreased the combined circular and random strategies of rat movement to find the hidden platform by 4%, 12%, and 18%, respectively, for the 2‐month OVX rats and by 8%, 25%, and 28%, respectively, for the 4‐month OVX rats. Thus, as noted earlier, the estrogenic activity of PU on the uterus weight or serum LH and FSH levels was not detected, and so the improvement in the impaired cognition in rats is likely to occur via other pathways, such as anti‐oxidant (Xie et al , ). The observed improvement in cognitive ability after E 2 or PU treatment, in terms of the higher latency and distance to find the platform, agreed with that previously reported in OVX mice (Xu et al , ) and Aβ‐induced cognitive impaired rats (Li et al , ).…”
Section: Discussionmentioning
confidence: 82%
“…Its medicinal value is bene ted from its wide range of pharmacological properties, such as vasodilation, cardio-protection, antioxidant, anti-apoptotic and reducing insulin resistance [15]. Puerarin plays a protective role against cell damage caused by pathological factors [16]. Puerarin has been reported to reduce Caspase-3 expression by activating PI3K/AKT signaling pathway, and signi cantly improve tumor necrosis factor-α (TNF-α) induced apoptosis in PC12 cells [17].…”
Section: Introductionmentioning
confidence: 99%